Pengembangan Media Busy Book Numbering dari Bahan Bekas untuk Pengenalan Matematika pada Anak Usia Dini - zikra hayati; Nida Jarmita; Putri Rahmi; Mardiani A (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2023)
Needing analysis of the lack in media, especially the introduction of children's mathematics, due to media in the form of posters, magazine, making children bored, that is not up to date in the learning process, the existing media has not been able to develop the competence of mathematical concepts appropriately, the media is still the same there is no upgrade, the media must be updated from the concept of number recognition for AUD and it is essential part to develop appropriate and holistic. It includes activities of Mathcing, Classification, Comparing, Ordering or Seriation. The objectives of this research are: (1) analyze the feasibility of developing busy book Numbering from Used Materials for the introduction of mathematics in children aged 5-6 years at Hafizul Ilmi Kindergarten. (2) describe the process of developing Busy Book Numbering from used materials for the introduction of mathematics in children aged 5-6 years at Hafizul Ilmi Kindergarten. This research uses R&D research by ADDIE model. The research instruments used in this study include: Busy Book Numbering Validation Feasibility Sheet and Observation Sheet of Math Recognition Ability for AUD. The results of the research are: Validation results obtained from media experts, 85% with very feasible criteria while for material experts 83,12% with feasible criteria. The implementation stage or trial conducted at Hafizul Ilmi Kindergarten obtained a percentage of 96% in very good developing criteria (BSB).